Method of auto-configuration for corporate proxies - Villarroel Acosta, Andrés Abelardo; Montenegro Marín, Carlos Enrique; Gaona García, Paulo Alonso; Nieto Acevedo, Yuri Vanessa (Ingeniería Solidaria, 2017)
Introduction: The proxy servers offer many advantages in business and academia. One of their main uses is to protect both the network and its users, offering a secure and fast connection to multiple users who require a service such as Internet. However, manual proxy settings require time and expertise by the end user, which leads to the network being less user friendly. The article was written in 2016 in the faculty of Engineering of the Universidad Distrital Francisco José de Caldas, Bogotá, Colombia.Methology: The paper has been elaborated at Colombia using a Cascade Model. Results: The article presents an introduction to proxy auto configuration and proxy servers, as well as a detailed explanation of the configuration methods.Conclusions: The study demonstrates methods and times that can lead to the reduction in standard connection time through manual configuration vs. automatic proxy configuration. This was implemented as a real case study in a company.
Keywords: dynamic host configuration protocol ( dhcp); proxy auto-configuration ( pac ); standard time; web proxy auto-discovery protocol ( wpad )